Haematophagous mites on poultry farms in the Republic of the Union of Myanmar. Issue 4 (April 2019) - Takehara, Masaki; Murata, Shiro; Katakura, Ken; Fujisawa, Sotaro; Hmoon, Myint Myint; Win, Shwe Yee; Bawm, Saw; Htun, Lat Lat; Aung, Ye Htut; Win, Mar Mar; Isezaki, Masayoshi; Maekawa, Naoya; et al.
Abstract: Haematophagous ectoparasites of poultry, such as Ornithonyssus sylviarum, northern fowl mites (NFMs), Dermanyssus gallinae, poultry red mites (PRMs), and Ornithonyssus bursa, tropical fowl mites (TFMs) are prevalent worldwide. Although poultry farming is a major industry in Southeast Asia, there are only a few reports concerning the prevalence of avian mites in this region. In this study, we sampled twenty farms in four major poultry farming areas in Myanmar. We detected the mites on six farms, and they showed morphological similarities to NFMs and TFMs. The nucleotide sequences of cytochrome c oxidase subunit I indicated that some mites were NFMs. This is the first report confirming the presence of NFMs and TFMs among the hematophagous mites infesting chickens on Myanmar poultry farms.